Purchase Decision Produk HLOUTFIT.ID: Peran Brand Awareness dalam Memediasi Content Marketing - Ni Kadek Nolla Hari Saputri; I Gusti Ayu Tirtayani; Desak Made Febri Purnama Sari; Made Mulyadi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The development of e-commerce on the TikTok Shop platform requires a deeper understanding of the relationship between content marketing strategy and consumer purchase decisions. This research aims to analyze the effect of Content Marketing on Purchase Decision with Brand Awareness as a mediating variable on HLOUTFIT.ID products in Bali Province. The research method uses a quantitative associative approach with a sample of 130 respondents selected through purposive sampling. Primary data were collected through online questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The research results show Content Marketing has a significant effect on Brand Awareness (t=19.945; p=0.000), Brand Awareness has a significant effect on Purchase Decision (t=1.998; p=0.046), and Content Marketing has a significant effect on Purchase Decision (t=13.846; p=0.000). Brand Awareness partially mediates the effect of Content Marketing on Purchase Decision with VAF value of 20.5 percent. The research model explains 74 percent of Brand Awareness variation and 66.3 percent of Purchase Decision variation. In conclusion, Content Marketing through the formation of strong Brand Awareness can increase Purchase Decision of consumers on HLOUTFIT.ID products, with recommendations for optimizing consistent and creative content to enhance the effectiveness of digital marketing.